Persepsi Masyarakat Kelurahan Nan Balimo Kota Solok terhadap pelaksanaan fungsi kehumasan pada bagian Humas Sekretariat Daerah Kota Solok - Nurul Afriyanti; Sulastri Sulastri; Ahmad Sabandi; Hanif Al Kadri (Journal of Educational Administration and Leadership, 2021)
This research is based on the results of the author’s observations on the implementation of public relations functions that are still not running effectively in the public relations section of the Solok City Regional Secretariat. The purpose of this research is to get information about the public perception of Nan Balimo Kota Solok village towards the implementation of public relation functions in the public relations section of the Solok City Regional Secretariat seen from indicators of creating a conducive atmosphere, effective communication, developing a positive organizational image, public persuasion, and fostering good relations with the public. This type of research is descriptive with quantitative methods. The population of this study was 2,502 people in Nan Balimo Village, so the sample was 259 respondents. Sample withdrawal in this study was proportional simple random sampling technique. Data collection in this research using questionnaires with likert scale has been tested validity and reliability. The average formulation is used in processing data in this research. The data showed the public response regarding the implementation of public relations function of the Solok City regional secretariat from: (1) creating a conducive atmosphere to get an average score of 3.90 that got a good category;(2) effective communication gets an average score of 3.88 which gets a good category; (3) develop a positive organizational image with an average score of 3.81 thats gets a good category; (4) public persuasion getas an average score of 3.79 which gets a good category; (5) fostering good relations with the public gets an average score of 3.76 which gets a good category. Overall, the public perception of Nan Balimo Kota Solok village towards the implementation of public relations function in the public relations section of the Solok City Regional Secretariat received an average score of 3.83 which got a good category.